ANALISIS POLA KESALAHAN JAWABAN SISWA PADA MATERI HITUNGAN KIMIA - Abdullah Abdullah; Johni Azmi; Ardiansyah Ardiansyah (Orbital: Jurnal Pendidikan Kimia, 2021)
Chemical calculation is the most important subject in learning chemistry but it is difficult understand for some students. Students will master chemistry well if this subject has been mastered well. Therefore, it is necessary to analyze student errors in mastering this material to assist students in their learning. This study aims to identify patterns of student error in solving chemical calculation problems. Students' conceptual errors were analyzed using the Newmann procedure. The error patterns analyzed include several errors, namely Reading, Comprehension, Transformation, Process Skills, and Encoding. Most of the students experienced a pattern of transformation errors on each item given. The largest percentage of transformation errors is in question number 3, which is 52.5%. This shows that the ability of students is still weak in solving problems related to chemical calculations. This study suggest that chemistry teachers emphasize more on students about the correct approach in solving chemical calculation problems.